Maverick: Making sense of a conjecture of antitrust policy in the lab - Christoph Engel; Axel Ockenfels (Max Planck Institute for Research on Collective Goods, 2013)
Antitrust authorities all over the world are concerned if a particularly aggressive competitor, a maverick, is bought out of the market. One plausible determinant of acting as a maverick is behavioral: the maverick derives utility from acting competitively. We test this conjecture in the lab. In a pretest, we classify participants by their social value orientation. Individuals who are rivalistic in an allocation task indeed bid more aggressively in a laboratory oligopoly market. Yet we also observe that the suppliers' willingness to pay to buy the maverick out of the market is much smaller than the gain from doing so. Again, rivalry contributes to the phenomenon: a supplier who buys out the maverick would fall behind the remaining competitor in terms of profits, which does not seem acceptable to most suppliers.
Keywords: D43; K21; L13; L41; C91; D03; D22; 330; oligopoly; aggressive sales; maverick; merger; buyout; social value orientation; rivalry